Editorial. Issue 1 (1st March 2023) - Chua, Liana; Buitron, Natalia; Cooper, Timothy
Abstract : Welcome to the first CJA issue of 2023 and the first to be produced by the new editorial team of Liana Chua (Editor), Natalia Buitron (Editor from October 2023) and Timothy Cooper (Reviews Editor). We have learnt a lot while sliding into our new roles, and we are immensely grateful to Andrew Sanchez and Tom White for leaving the journal in such excellent shape, Claudia Luna for her editorial assistance, and Janine Latham, Sascha Berghahn and the rest of the Berghahn team for their cheerful support and patience.